Recaudación de créditos otorgados a los socios de la Cooperativa de Ahorro y Crédito “El Cafetal” del cantón Babahoyo, en el periodo 2020-2021. - Vélez Ulloa, Katherine Lissette (2022)
The Savings and Credit Cooperative "El Cafetal" of the Babahoyo Canton, is a voluntary organization open to all those willing to use its services and willing to accept the responsibilities that membership entails without discrimination of gender, race, social class, political position or religious. Through the implemented research technique, it was possible to detect that one of the most representative problems in the Cooperative is the delay in the payment of the credits that are granted to the partners, the delinquency for not canceling, mortgage debts, among others. All this affects the bank's portfolio and its transactional operations, on the other hand, the Cooperative does not have a good planning so that its members pay on time or within the established terms the fees that are presented in said agreement.